SISTEM PENGENDALIAN MANAJEMEN PADA BALAI LATIHAN PENDIDIKAN TEKNIK (BLPT) GMIM KAATEN TOMOHON - Graini Tifani Lumenta; Leonardus Ricky Rengkung; Celcius Talumingan (Sam Ratulangi University, 2017)
This study aims to measure Management Control Systems at BLPT Kaaten Tomohon. This research lasted for 3 months, carried out at Training Center Technical Education (BLPT) Kaaten Tomohon which is located in Matani I, Jln Raya Tomohon-Tondano. The data used are the primary data taken in relation to two kinds of products as a superior product ie table products (dining table and guest table) and chair products (church chairs) in one production process. Data analysis used in this research is quantitative analysis by calculating contribution contribution of Revenue Center, Cost Center and Profit Center of each product, while Investment Center is calculated based on R / C ratio. The result Chairs Dining Table products are profitable products and contribute greatly to the mainstay products at BLPT Kaaten Tomohon.